Dietary sugars, not lipids, drive hypothalamic inflammation - Gao, Yuanqing; Fleming, Thomas; Nawroth, Peter Paul (Molecular metabolism, 2017)
Objective: The hypothalamus of hypercaloric diet-induced obese animals is featured by a significant increase of microglial reactivity and its associated cytokine production. However, the role of dietary components, in particular fat and carbohydrate, with respect to the hypothalamic inflammatory response and the consequent impact on hypothalamic control of energy homeostasis is yet not clear. Methods: We dissected the different effects of high-carbohydrate high-fat (HCHF) diets and low-carbohydrate high-fat (LCHF) diets on hypothalamic inflammatory responses in neurons and non-neuronal cells and tested the hypothesis that HCHF diets induce hypothalamic inflammation via advanced glycation end-products (AGEs) using mice lacking advanced glycation end-products (AGEs) receptor (RAGE) and/or the activated leukocyte cell-adhesion molecule (ALCAM). Results: We found that consumption of HCHF diets, but not of LCHF diets, increases microgliosis as well as the presence of N(ε)-(Carboxymethyl)-Lysine (CML), a major AGE, in POMC and NPY neurons of the arcuate nucleus. Neuron-secreted CML binds to both RAGE and ALCAM, which are expressed on endothelial cells, microglia, and pericytes. On a HCHF diet, mice lacking the RAGE and ALCAM genes displayed less microglial reactivity and less neovasculature formation in the hypothalamic ARC, and this was associated with significant improvements of metabolic disorders induced by the HCHF diet. Conclusions: Combined overconsumption of fat and sugar, but not the overconsumption of fat per se, leads to excessive CML production in hypothalamic neurons, which, in turn, stimulates hypothalamic inflammatory responses such as microgliosis and eventually leads to neuronal dysfunction in the control of energy metabolism.
Available online 20 June 2017
Gesehen am 19.06.2018